MEDIEVAL EPIGRAPHS OF KHNOV VILLAGE (11th–15th CENTURIES): NEW DATA - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2020)
The history of studying rich epigraphic heritage of the ancient Dagestan village of Khnov spans over half a century. The overwhelming majority of the village’s epigraphic monuments are written in Arabic. Our all-round study of Khnov inscriptions revealed a number of previously undocumented monuments. The aim of the paper is to present the results of studying Khnov inscriptions of the 11th–15th centuries. They cover various genres of epigraphy: construction, religious and didactic texts, inscriptions-epitaphs. Newly revealed Kufic inscriptions are introduced into science, dating back according to paleographic indicators to the 11th–12th centuries. With good reason they can be considered the most ancient monuments of Kufic writing from Khnov. The early existence of the minaret in Khnov is evidenced by the newly discovered inscription of the 14th–15th centuries. In addition, we propose a new reading, interpretation or alternative dating of a number of Khnov inscriptions already known to science from the 12th–15th centuries. Among them are a well-known inscription of 1401 about the construction of a minaret, Kufic inscriptions of epigraphic frieze of the mosque of the Western quarter, epitaphs on tombstones of the 14th–15th centuries. It has been established that the writing style of the Kufiс inscriptions of the frieze differs from each other, which may indicate both the different time nature of their creation and the work of different calligraphers. The inscriptions of the epigraphic strips of some gravestones were read for the first time. The proposed new dating of one of the epitaphs makes it the oldest surviving dated epitaph in Khnov (1355). The paper contains results of the prosopographic study of the whole set of Khnov inscriptions, including epigraphy, not mentioned in the study. The new data on the medieval epigraphy of the village of Khnov, presented in the paper, expand the source base for research on the history and culture of the region and can serve as the basis for future historical reconstructions.
Keywords: Dagestan; Khnov village; epigraphy; Middle Ages; construction inscriptions; epitaphs; amir; Kufi; Naskh.